PEMBELAJARAN MAHARAH KALAM DENGAN STRATEGI RECIPROCAL TEACHING MENGGUNAKAN MEDIA TIKTOK DI MA ARRAHMAN PALEMBANG - M. Sony Anjang Sono; Kristina Imron; Muhammad Alfath Qaaf (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to test the effectiveness of the use of the Reciprocal Teaching strategy integrated with TikTok media in learning Maharah Kalam (speaking skills) of students at MA Arrahman Palembang. Speaking skills are a crucial aspect of language for everyday communication, but in practice it is often considered difficult and taught using monotonous conventional methods, resulting in low student learning outcomes. The Reciprocal Teaching strategy offers a constructivist approach that emphasizes four cognitive components (summarizing, asking, clarifying, and predicting) that students carry out in turns. The use of TikTok media, which is popular among teenagers, was chosen to increase creativity, interaction, and learning motivation through a short, audio-visual and engaging video format. This study uses a mixed method approach with a One Group Pretest-Posttest Design to compare students' Maharah Kalam abilities before and after treatment. The final results of the study are expected to show a significant increase in students' Maharah Kalam abilities, proving that this combination of strategies and media is effective as a learning innovation.